If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 35 = 14x + -36 Reorder the terms: 35 + 5x = 14x + -36 Reorder the terms: 35 + 5x = -36 + 14x Solving 35 + 5x = -36 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 35 + 5x + -14x = -36 + 14x + -14x Combine like terms: 5x + -14x = -9x 35 + -9x = -36 + 14x + -14x Combine like terms: 14x + -14x = 0 35 + -9x = -36 + 0 35 + -9x = -36 Add '-35' to each side of the equation. 35 + -35 + -9x = -36 + -35 Combine like terms: 35 + -35 = 0 0 + -9x = -36 + -35 -9x = -36 + -35 Combine like terms: -36 + -35 = -71 -9x = -71 Divide each side by '-9'. x = 7.888888889 Simplifying x = 7.888888889
| 1+2[3(x-1)-5(2x-3)]=2x-7 | | 4x+5-10x=8+3x+12 | | 5x+31=tx+11 | | 4x^2+7x-8=0 | | 8b-4(b-2)=42 | | -6-20=-2n | | 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 | | 51-81.623= | | 0=(.25x^4)-(2x^2)-1 | | 7.2g+1.5=6+3.2g | | 2x^2+4x-10=0 | | 5x+2(x-3)=12x-5+14 | | 4(2x+3)-6x=18 | | -8x-(3x+6)=44-x | | 2t(t+5)+1=3t-3-t^2 | | 4x+4+2x= | | -3x+6=-3x+9 |